The effect of Hydrogen-rich „Truskavetska” bottled water on the swimming stress test in female rats - Walery Zukow; Igor Popovych (Journal of Education, Health and Sport)
Background and aim. Despite the use of drinking hydrogen rich water both in clinical and sports medicine, further research into the mechanisms of its beneficial effect remains relevant. We found that both Naftussya bioactive water per se and combined balneotherapy have an ambiguous effect on physical performance. It was also found that the preventive use of “Truskavetska” bottled water, the chemical composition of which is somewhat similar to that of Naftussya bioactive water, has both similar and different effects on the post-stress parameters of rats. We set ourselves the goal of finding out the possibility of correcting the effect of "Truskavetska" bottled water on the post-stressor state of the neuro-endocrine-immune complex, as well as the endurance of rats by enriching it with hydrogen.